Novel Approach of Robust Hinf Tracking Control for Uncertain Fuzzy Descriptor Systems Using Parametric Lyapunov Function - Anh, Ho Pham Huy; Kien, Cao Van (Journal of Computer Science and Cybernetics, 2020)
This paper proposes a novel uncertain fuzzy descriptor system which is an extension from standard T-S fuzzy system. A fixed Lyapunov function-based approach is considered and controller design for this rich class of fuzzy descriptor systems is formulated as a problem of solving a set of LMIs. The design conditions for the descriptor fuzzy system are more complicated than the standard state-space-based systems. However, the descriptor fuzzy system-based approach has the advantage of possessing fewer number of matrix inequality conditions for certain special cases. Hence, it is suitable for complex systems represented in descriptor form which is often observed in nonlinear mechanical systems.